Common chromosome fragile sites in human and murine epithelial cells and FHIT/FRA3B loss‐induced global genome instability. Issue 11 (9th August 2013) - Hosseini, Seyed Ali; Horton, Susan; Saldivar, Joshua C.; Miuma, Satoshi; Stampfer, Martha R.; Heerema, Nyla A.; Huebner, Kay
<x xml:space="preserve">Abstract</x> Chromosomal positions of common fragile sites differ in lymphoblasts and fibroblasts, with positions dependent on the epigenetically determined density of replication origins at these loci. Because rearrangement of fragile loci and associated loss of fragile gene products are hallmarks of cancers, we aimed to map common fragile sites in epithelial cells, from which most cancers derive. Among the five most frequently activated sites in human epithelial cells were chromosome bands 2q33 and Xq22.1, which are not among top fragile sites identified in lymphoblasts or fibroblasts. FRA16D at 16q23 was among the top three fragile sites in the human epithelial cells examined, as it is in lymphoblasts and fibroblasts, while FRA3B at 3p14.2, the top fragile locus in lymphoblasts, was not fragile in most epithelial cell lines tested. Epithelial cells exhibited varying hierarchies of fragile sites; some frequent epithelial cell fragile sites are apparently not frequently altered in epithelial cancers and sites that are frequently deleted in epithelial cancers are not necessarily among the most fragile. Since we have reported that loss of expression of the FRA3B‐encoded FHIT protein causes increased replication stress‐induced DNA damage, we also examined the effect of FHIT‐deficiency on markers of genome instability in epithelial cells. FHIT‐deficient cells exhibited increases in fragile breaks and in γH2AX and 53BP1 foci in G1 phase cells, confirming in epithelial cells that the FHIT gene and encompassing FRA3B, is a "caretaker gene" necessary for maintenance of genome stability. © 2013 Wiley Periodicals, Inc.